2014
DOI: 10.1534/genetics.114.165720
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic Mutations Are Subject to Strong Stabilizing Selection

Abstract: The assumption that pleiotropic mutations are more deleterious than mutations with more restricted phenotypic effects is an important premise in models of evolution. However, empirical evidence supporting this assumption is limited. Here, we estimated the strength of stabilizing selection on mutations affecting gene expression in male Drosophila serrata. We estimated the mutational variance (V M ) and the standing genetic variance (V G ) from two well-matched panels of inbred lines: a panel of mutation accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 72 publications
2
44
1
Order By: Relevance
“…Importantly, Runcie and Mukherjee (2013) found that this was one of only two factors that were genetically correlated with a measure of competitive fitness. Studies in a variety of taxa have suggested a general pattern across many genes of stabilizing selection on expression levels (Denver et al 2005;Rifkin et al 2005;Bedford and Hartl 2009;Warnefors and Eyre-Walker 2012), and we have recently demonstrated that stabilizing selection is intensified in the presence of pleiotropic effects across traits (McGuigan et al 2014a). This emergent picture of general transcriptome-wide mechanisms of gene regulation across many traits also provides a potential basis for the ubiquitous presence of correlated responses in both evolutionary experiments and applied animal and plant breeding.…”
Section: The Extent Of Genetic Covariance Among Gene Expression Traitsmentioning
confidence: 81%
See 1 more Smart Citation
“…Importantly, Runcie and Mukherjee (2013) found that this was one of only two factors that were genetically correlated with a measure of competitive fitness. Studies in a variety of taxa have suggested a general pattern across many genes of stabilizing selection on expression levels (Denver et al 2005;Rifkin et al 2005;Bedford and Hartl 2009;Warnefors and Eyre-Walker 2012), and we have recently demonstrated that stabilizing selection is intensified in the presence of pleiotropic effects across traits (McGuigan et al 2014a). This emergent picture of general transcriptome-wide mechanisms of gene regulation across many traits also provides a potential basis for the ubiquitous presence of correlated responses in both evolutionary experiments and applied animal and plant breeding.…”
Section: The Extent Of Genetic Covariance Among Gene Expression Traitsmentioning
confidence: 81%
“…The relative rate of mutation in individual traits compared to genome-wide estimates and the strength of stabilizing selection acting on highly heritable quantitative traits are both observations that are difficult to explain without extensive pleiotropy among traits, reducing the number of genetically independent traits (Johnson and Barton 2005). In support of these two inferences, mutational pleiotropy among gene expression traits is widespread, with single putative mutations affecting many traits, even when those traits are considered without regard to known biological function (McGuigan et al 2014b), and mutations are under stronger stabilizing selection when they are pleiotropic (McGuigan et al 2014a). However, empirical studies specifically targeting high-dimensional phenotypes are required to characterize the extent of pleiotropy across the phenome.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the estimation of both mutational and additive genetic variance from the same data, within the same model, will provide the most direct and biologically relevant determination of the average selection against mutations (s = V M /V A ). Although prominent in the theoretical literature (Kondrashov and Turelli 1992), these parameters have been determined relatively few times, and current estimates typically depend on genetic and mutational parameters measured in different populations (and in some cases at different times using different experimental protocols in different laboratories), with mutational parameter estimates derived from inbred lines (Houle et al 1996;Denver et al 2005;McGuigan et al 2014). The simultaneous estimation of standing genetic and mutational variance from the same outbred population also allows a direct quantitative assessment of the theoretical models of mutation-selection balance that attempt to explain equilibrium levels of additive genetic variance (Turelli 1984;Lynch and Hill 1986;Bürger 2000;Johnson and Barton 2005).…”
mentioning
confidence: 99%
“…First, that there is more genetic variance for the expression of male-biased genes and therefore greater evolutionary potential (Fisher 1932). Second, that malebiased genes are less constrained by between-trait pleiotropy (the degree to which a single gene affects multiple traits) (Fisher 1930;Mank et al 2008b;Blows and Walsh 2009;Assis et al 2012;Innocenti and Chenoweth 2013;McGuigan et al 2014) and/or less constrained by the fact that males and females share a genome (between-sex pleiotropy measured as the between-sex genetic correlation for expression, r(m,f)) (Lande 1980;Lande 1987;Griffin et al 2013). In addition, by integrating r(m,f) estimates with clinal divergence data, I also test the hypothesis raised in Chapter 3, that correlated divergence in males and females, which resulted in an apparent lack of sex-specific divergence, was possibly due to the shared genome constraining the independent divergence of males and females.…”
Section: Sex-biased Transcriptome Divergence Along a Latitudinal Gradmentioning
confidence: 99%
“…Second, it is possible that male-biased genes evolve faster than other classes of gene because they are less genetically constrained by pleiotropy (the degree to which a single gene affects multiple traits) (Mank et al 2008b;Blows and Walsh 2009;Meisel 2011;Assis et al 2012;Innocenti and Chenoweth 2013;McGuigan et al 2014). Pleiotropy could constrain evolution because of widespread multivariate stabilising selection, where, for example, an increase in expression of a gene could shift some traits closer to their optima while simultaneously pulling other traits away, the so called 'cost of complexity' (Fisher 1958;Lande 1980;Waxman and Peck 1998;Orr 2000).…”
Section: Introductionmentioning
confidence: 99%